Exciton dynamics in colloidal quantum-dot leds under active device operations - Shendre, Sushant (2019)
Colloidal quantum-dot light-emitting diodes (QLEDs) are lucrative options for color-pure lighting sources. To achieve high-performance QLEDs, besides developing high-efficiency quantum dots (QDs), it is essential to understand their device physics. However, little understanding of the QD emission behavior in active QLEDs is one of the main factors hindering the improvement of device efficiency. In this work, we systematically studied the exciton dynamics of gradient composition CdSe@ZnS QDs during electroluminescence in a working QLED. With time-resolved photoluminescence analyses using fluorescence lifetime imaging microscopy we analyzed a large population of QDs spatially spreading over an extended area inside and outside the device. This allows us to reveal the statistically significant changes in the behavior of QD emission in the device at different levels of applied voltages and injection currents. We find that the QD emission efficiency first drops in device fabrication with Al electrode deposition and that the QD exciton lifetime is then statistically reduced further under the QLED’s working conditions. This implies the nonradiative Auger recombination process is active in charged QDs as a result of imbalanced charge injection in a working QLED. Our results help to understand the exciton behavior during the operation of a QLED and demonstrate a new approach to explore the exciton dynamics statistically with a large QD population.